Subtle othering in EFL group work - Widyastuti, Susana (Diksi, 2023)
Group work in language learning has been praised for its success stories in encouraging collaboration and interaction among learners. However, a scant attention has been given to explore how students perceive the Other and how group work can be a platform for identity construction. Within the context of EFL classroom where different cultures and values interact, this study focuses on students' preference towards group work and peers, which is reflected through their perception and behaviours towards different attributes of the constructed Self and Other. The data were collected through questionnaires involving 241 students of English Literature Study Program at a state university in Indonesia. The results show that, first, despite the challenges to embrace difference among the members, group work is still preferred over individual work for the advantages, productivity, and enjoyment it offers. Second, while friendship is seen as a crucial contributor for a successful group work, students choose peers based on personalities and skills on English language, teamwork, communication, leadership, and technology. This preference motivates stereotyping and othering, whereby the good characteristics of the preferred Self are contrasted with the bad qualities of the dis-preferred Other. This study has proven that subtle othering prevails in group work practices in the academic environment and that such othering practices have influenced students' behaviours, roles, and abilities to engage and succeed in group work. Pedagogical attempts should be devoted to decrease othering, so as to foster awareness towards difference, in order to create a more accommodative environment for language learning.